(untitled) (London Journal of Medical and Health Research, 2025)
BACKGROUND: Penetrating macular holes of the retina remain today one of the main reasons for a significant loss of central vision, especially in working age patients. At the same time, the mainstream problem are the validity and effectiveness of treatment of large and giant macular holes with a diameter of more than 5001000 m. AIM: to optimize the treatment method for patients with large and long-standing macular holes. To analyze the results of treatment of patients with this condition. MATERIALS AND METHODS: In 2023, 56 patients were operated on for idiopathic large macular hole. During vitrectomy, a new surgical technique was used for the macular hole bed tamponade with flaps of the internal limiting membrane in combination with the introduction of platelet-rich plasma. RESULTS: After the resorption of the gas-air mixture (11.5 months after surgery), ophthalmoscopically and according to optical coherence tomography data, closure of the macular hole was observed in 51 of 56 operated patients, which amounted to 91.1%. CONCLUSIONS: The surgical treatment technique used allows for closure of large macular holes in 91.1%.